Covid-19 dan Efusi Pleura - Cut Sarah Faradilla; Marliza Marliza (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
COVID-19 and pleural effusion are respiratory diseases which are currently still a matter of public concern due to their progression which can cause death if not treated quickly and appropriately. COVID-19 is a pandemic disease that was first reported to have appeared at the end of 2019. Even though the status of COVID-19 has now changed to an endemic disease, transmission is still occurring globally so it will continue. Symptoms that appear in patients with COVID-19 generally include shortness of breath, dry cough, fever and fatigue. Pleural effusion is a condition of fluid accumulation that exceeds normal limits in the pleural cavity between the parietal pleura and the visceral pleura. This fluid can be in the form of transudate or exudate fluid. This buildup of fluid can occur due to an imbalance between the production and excretion of fluid in the pleural cavity. Symptoms that arise due to pleural effusion are shortness of breath, chest pain, coughing or pleuritic chest pain. Pleural effusion is also a complication of COVID-19. There has been an increase of 404 new infections in COVID-19 in Indonesia as of January 2024 according to the latest epidemiological data, but there are no published figures for pleural effusion in Indonesia.